2014
DOI: 10.1186/1752-0509-8-68
|View full text |Cite
|
Sign up to set email alerts
|

Modelling human protein interaction networks as metric spaces has potential in disease research and drug target discovery

Abstract: BackgroundWe have recently shown by formally modelling human protein interaction networks (PINs) as metric spaces and classified proteins into zones based on their distance from the topological centre that hub proteins are primarily centrally located. We also showed that zones closest to the network centre are enriched for critically important proteins and are also functionally very specialised for specific ‘house keeping’ functions. We proposed that proteins closest to the network centre may present good ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The starting point is that in all the networks under consideration, the centres were identified, and nodes were grouped (in zones) according to the distances they are from these central proteins. With this classification, functional enrichment was performed and biological hypotheses were drawn 9 25 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The starting point is that in all the networks under consideration, the centres were identified, and nodes were grouped (in zones) according to the distances they are from these central proteins. With this classification, functional enrichment was performed and biological hypotheses were drawn 9 25 .…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been observed that there is some level of specialization by proteins in various zones of the HFPIN 25 . Also, while some pathways cut across zones, of importance is that sensing pathways are far more pronounced in central zones than in periphery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This property may be helpful when prioritizing between multiple genes in a disease module for functional and clinical studies, as well as when selecting genes as potential drug targets. It is interesting that genes targeted by drugs are more likely to be hubs . The network property that highly interconnected nodes are likely to be functionally related can be exploited to find novel diagnostic markers and therapeutic targets amongst the interactors of known disease genes .…”
Section: Basic Clinical and Pharmacological Implications Of Disease mentioning
confidence: 99%